GAMBARAN SEKTOR INFORMAL NELAYAN KELURAHAN CILINCING JAKARTA UTARA SEBAGAI CALON PESERTA BPJS KESEHATAN - Dara Lutfiana; Chriswardani Suryawati; Eka Yunila Fatmasari (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
JKN implementation in Indonesia is targeting the coverage nationwide in 2019. Informal workers who predominate in Indonesia is a challenge for Health BPJS in achieving these targets. Of the 67.87 million informal workers 30% of whom are fishermen, it means that fishermen plays an important role in achieving the target JKN membership, then the condition of the fishermen need to be studied further to expand the coverage of informal participants in JKN. The purpose of this study was to describe the characteristics, knowledge, interests, socialization model, and the ability to pay fishermen to JKN. This research is descriptive through a quantitative of cross-sectional approach. The sample included 100 fisherman and 4 informants consisting of administrative staff, KUB chairman and coordinator of the fishermen. The results showed that respondents have characteristics that are 62% aged 20-40 years, 45% complete elementary school, 75% have a little amount of family burden (≤ 4 people), 55% have revenues below KHL standard, and 57% are fisherman user. 54% of respondents have enough knowledge about JKN, 92% have high interest in JKN, 69% respondent have family ATP ≤ contribution fare of JKN, 44% know JKN first time through friends, 98% have never get JKN socialization, 57% chose discussion as a form of socialization, 60% stated that socialization can be done both weekdays and weekends, 33% chose the afternoon as socialization time, and 82% are willing to attend socialization JKN. It is recommended that the government mapping informal sector fishermen, the fishermen need to be considered as PBI participants, socialization and the media JKN need to be implemented, as well as Health BPJS to pick up the ball in terms of enrollment JKN.